2017
DOI: 10.1016/j.rgg.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and evolution of high-pCO2 groundwaters of the Mukhen spa (Russian Far East)

Abstract: We present the chemical and isotope compositions of the water and gas phases of the unique Mukhen cold high-pCO2 spa. Estimated δ18O, δD, and δ13CTIC values and data on geology and hydrogeology of the studied area indicate that the source of the groundwaters is meteoric waters, whereas carbon dioxide is of deep genesis and numerous regional faults are gas-feeding channels. Calculations of equilibrium reactions in the water–rock system show that the upper-aquifer waters (HCO3–Ca–Mg) with low TDS are undersatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…As can be seen from Figure 6, geothermal water in the study area falls near the GMWL line, indicating that the main recharge source of geothermal water in the study area is atmospheric precipitation. However, the 18 O of the Yaoshuitan carbonated thermal water spring has an obvious negative drift, which is because the geothermal spring contains a large amount of C 16…”
Section: ) Water-rock Interaction and Evolution Processmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Figure 6, geothermal water in the study area falls near the GMWL line, indicating that the main recharge source of geothermal water in the study area is atmospheric precipitation. However, the 18 O of the Yaoshuitan carbonated thermal water spring has an obvious negative drift, which is because the geothermal spring contains a large amount of C 16…”
Section: ) Water-rock Interaction and Evolution Processmentioning
confidence: 99%
“…Italiano et al (2016) studied the geochemical characteristics and genesis of dissolved gasses in the eastern Carpathian Mountains, Transylvania Basin, Romania, and pointed out that in addition to obvious atmospheric gas sources, volcanic and crustal gas sources provide materials for circulating groundwater [15]. Shvartsev et al (2017) analyzed the origin and evolution of the high pCO 2 groundwater in the Mukhen geothermal springs in the Russian Far East [16]. Kharaka et al (2018), through an experiment on the reaction between groundwater and CO 2 , showed that the leakage of CO 2 into groundwater increased acidity, which increased the content of Fe and other metals in groundwater [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Mukhen spa is located on the border of the Middle Amur sedimentary basin, which is part of a complex geologic structure, and the large Sikhote-Alin mountain-folded system (Fig.1). The geological structure of the region is formed by Mesozoic basement, Oligocene-Miocene sedimentary and volcanic rocks, Pliocene-Lower Quaternary flood basalts, and Quaternary alluvium [1,2]. The Mesozoic rocks are represented by the terrigenous sediments of the basement which are intruded by dikes of granodiorite, graniteporphyry, and layers of siltstones and sandstones.…”
Section: Geologymentioning
confidence: 99%
“…The most phenomenal and popular sparkling groundwaters in the northern part of the Sikhote-Alin territory are in the Mukhen spa which is located at about 100 km from Khabarovsk (Fig.1). The chemical composition of the Mukhen spa water is unique because of two different types of cold CO2-rich groundwaters circulating in the same area [1,2]. This study was undertaken to identify the source of water and gas phases of the Mukhen spa.…”
Section: Introductionmentioning
confidence: 99%
“…К сожалению, продолжительное время считалось, что такое взаимодействие не может долго продолжаться, поскольку растворимость алюмосиликатов очень мала и быстро наступает равновесие с ними водного раствора. И только в последнее время нам удалось показать, что все наоборот: равновесие природной воды с такими минералами не достигается никогда [Shvartsev, 1998[Shvartsev, , 2010[Shvartsev, , 2015Shvartsev et al, 2007Shvartsev et al, , 2017Plyusnin et al, 2013].…”
Section: внутренняя эволюция системы вода -порода -газunclassified